Improved survival and neurological outcomes with lysophosphatidylcholine supplementation in severe cardiac arrest model - Shoaib, Muhammad; Nishikimi, Mitsuaki; Choudhary, Rishabh C.; Yagi, Tsukasa; Hayashida, Kei; Yin, Tai; Espin, Blanca B.; Becker, Lance B.; Kim, Junhwan (Frontiers in Pharmacology, 2025)
Cardiac arrest (CA) results in a loss of blood circulation, leading to whole-body ischemia-reperfusion injuries. A deficiency in plasma lysophosphatidylcholine (LPC) levels has been observed in both human patients and rat models and is implicated in organ dysfunction following CA. Building on previous findings from a mild injury model, this study explored the therapeutic potential of LPC supplementation in a severe 12-min rat CA model. The study also compared the effects of combining multiple LPC species with individual species to better determine the most effective strategy and enhance the translational potential of LPC therapy for CA treatment. We found that LPC supplementation, particularly with LPC(18:1) alone and in combination with other LPC species, significantly improved 72-h survival rates. However, combination therapy offered superior protection compared to single LPC species, as assessed by modified neurological deficit score (mNDS). Additionally, combination therapy reduced troponin I levels, indicating cardioprotection, and facilitated the return of the N10 peak in somatosensory evoked potentials, suggesting preserved nervous system integrity. While individual LPC species offered some benefits, combination therapy yielded superior results. The significant improvements in outcomes observed in this severe model highlight the robustness of LPC therapy and its potential to treat CA patients with varying injury severities. Specifically, the use of LPC in combination emerges as a promising strategy for mitigating organ damage and enhancing recovery outcomes post-CA.